Impact of Conscious Self-Regulation, Engagement and Motivation on Academic Performance of Schoolchildren During Different Periods of Study - Ishmuratova, Y.A.; Potanina, A.M.; Bondarenko, I.N. (Psihologičeskaâ nauka i obrazovanie, 2021)
The paper is devoted to the problem of the relationship between conscious self-regulation, school engagement and motivation, as well as the specifics of their contributions to the academic performance of schoolchildren during different pe-riods of study. For the first time, a 5-factor structure of the relationship between self-regulation, engagement, personality traits, and academic motivation was described in a sample of 1103 students in grades 5—11 of general education schools. We evaluated the contribution of these factors to the academic achieve¬ment of students in three periods of school education (in middle school, during the transition from middle to high school, and in high school). It is shown that the factors “Goal-setting and engagement” and “Cognitive and social activity”, which include regulatory, motivational, personality features and engagement, make a significant contribution to the academic performance of students, regardless of the period of learning. Regulatory processes of modelling significant condi¬tions for achieving the goal and evaluating the results as part of the “Operational Regulation” factor provide high achievement for students in grades 5—6. We also revealed the negative influence of the “External Motivation” factor on the aca¬demic performance of high school students and the positive contribution of the “Neuroticism and Anxiety” factor to the annual final grades in this period of study. The results are discussed in the context of age-related and educational tasks that are solved by students during school education. Представлены результаты исследования проблемы взаимосвязи осознан¬ной саморегуляции, школьной вовлеченности и мотивации, а также спец¬ифики их вкладов в академическую успеваемость школьников в разные периоды обучения. На выборке 1103 учащихся 5—11 классов общеобра¬зовательных школ впервые показана 5-факторная структура взаимосвязи саморегуляции, вовлеченности, личностных свойств и академической мотивации. Оценен вклад этих факторов в академические достижения уча¬щихся в трех периодах школьного обучения (в средней школе, при переходе из средней в старшую школу и в старшей школе). Показано, что факторы «Целеполагание и вовлеченность», «Познавательная и социальная актив¬ность», включающие в себя регуляторные, мотивационные, личностные свойства и вовлеченность, вносят значимый вклад в академическую успе¬ваемость учащихся независимо от классов обучения. Регуляторные про¬цессы моделирования значимых условий достижения цели и оценки резуль-татов в составе фактора «Оперативная регуляция» обеспечивают высокие оценки у учащихся 5—6 классов. Выявлены негативное влияние фактора «Внешняя мотивация» на успеваемость старшеклассников и позитивный вклад фактора «Нейротизм и тревожность» в годовые итоговые результаты в этом периоде обучения. Полученные результаты обсуждаются в контексте возрастных и учебных задач, которые решаются учащимися на протяжении школьного обучения.